Applying An Analytical Hierarchy Process For Strategic Decision-Making Of Business Solution To Address Sales Decline In SMEs: (Case study: TB. Buyung Mas Putri) - Perdana, I Komang Wira Yuda; Putro, Utomo Sarjono (Jurnal Manajemen Bisnis, 2024)
This research addresses the sales decline experienced by TB. Buyung Mas Putri, a retail building materials store in Indramayu, caused by inefficiencies in manual processes, the absence of digital marketing and e-commerce platforms, and disorganized financial reporting. Coupled with increasing market competition, these challenges have significantly impacted sales performance. However, the company’s strategic location, loyal customer base, and diverse product offerings present opportunities for recovery and sustainable growth. To address these issues, the study employs a combination of analytical methods: SWOT analysis to identify internal and external factors, TOWS matrix to develop actionable strategies, Kepner-Tregoe decision-making framework to prioritize solutions, Analytical Hierarchy Process (AHP) to evaluate and rank strategies, and Fishbone analysis to uncover the root causes of operational inefficiencies. The findings highlight four key strategies: automating inventory management to reduce stockouts and errors, implementing financial management tools to improve reporting and decision-making, collaborating with contractors to ensure steady demand and long-term partnerships, and adopting digital marketing and e-commerce platforms to expand market reach by implementing these strategies, TB. Buyung Mas Putri can enhance operational efficiency, restore sales growth, and establish a foundation for long-term success in a competitive retail market..